THE INDIVIDUAL STUDY - A TRANSVERSAL COMPETENCY OF STUDENTS. AN OBSERVATIONAL STUDY - DANA JUCAN (Studia Universitatis Babes-Bolyai, 2016)
ABSTRACT. In the present study we have defined individual study as being a transversal competency that implies an individual strategy for collecting data from various sources (notes, bibliography, textbook, dictionaries, compendiums, Internet, etc.), comprehending it, organizing and systematizing it, independently issuing hypotheses and their validation or invalidation through a personal self‑ imposed effort of a cognitive and metacognitive nature. We have undertaken a research effort in order to establish the importance accorded by students to the individual study, the extent to which the students possess information on the planning, organizing, and the development of the self‑study; the methods (modalities) of implementing the self‑study, the strategies for individual studying used by students, the modalities of taking notes, identifying the ways in which they study individually.